Advanced Cryptographic Techniques for Securing AI-Driven IoT Systems - Dr. Falguni Suthar; Ms. Hiralben Patel; Dr. Bhavesh Patel (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The convergence of Artificial Intelligence (AI) and Internet of Things (IOT) has inspired the emergence of artificial intelligence (AIOT) of things, a paradigm that integrates intelligent algorithms with interconnected equipment. While AIOT provides significant progress in automation and data processing, it introduces adequate safety challenges due to the transmission and processing of vast amounts of sensitive data. This research paper examines various cryptographic techniques that can be employed to increase security in the AIOT system. We analyze the weaknesses contained in AIOT architecture, discuss the role of cryptography in reducing these risks, and propose a framework to apply a strong cryptographic solution to the AIOT environment.